Polyherbal Extracts and its Potential Impact on Dandruff Causative Agent of Malassezia globosa (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
At present, more than quasi of the worldwide people deal with the major skin problem with dandruff. The presence of the Malassezia fungus suggestively subsidizes this condition by potentially generating the production of cytokines in keratinocytes, the cells responsible for synthesizing keratin and activating provocative alleyways. Antifungal activity of selected Indian medicinal plant extracts against the dandruff causing pathogen. The present work assigned the four experimental plants named Eclipta alba, Hibiscus rosasinensis, Lawsonia inermis and Muraya koenigii and its polyherbal mixed composition of these four herbal extracts. The prepared aqueous poly herbal extracts were added to the wells of Malassezia globossa inoculated plates. From the present antifungal result was clearly expressed all the four individual plant extract showed minimum to maximum antidandruff activity among the four M.koeningi possessed maximum antifungal activity than other three extracts. Even though, a mixed composition of these four herbal extracts (aqueous) contains the maximum potential antidandruff effect than the individual extracts of E.alba, H. rosasinensis, L. inermis. Hence, the present experimental four herbal extract was definitely depicted for great potential against the dandruff and skin pathogenic fungal organism of M. globossa.